48-Week Outcome after Cessation of Nucleos(t)ide Analogue Treatment in Chronic Hepatitis B Patient and the Associated Factors with Relapse - Wen-xiong Xu; Qian Zhang; Xiang Zhu; Chao-shuang Lin; You-ming Chen; Hong Deng; Yong-yu Mei; Zhi-xin Zhao; Dong-ying Xie; Zhi-liang Gao; Chan Xie; Liang Peng (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. We aimed to ascertain the feasibility and safety of NA cessation, the status of patients after cessation, and the predictive factors for relapse and subsequent retreatment. Methods. A total of 92 patients were enrolled in this prospective study. Patients were monitored every month for the first 3 months after cessation and every 3 months thereafter. Results. Sixty-two patients finished 48 weeks of follow-up. None died or developed liver failure, cirrhosis, or HCC. The 62 patients could be divided into 4 categories according to the 48-week clinical development of relapse. Virologic relapses occurred in 39 (62.9%) patients, with 72.7% occurring in the first 24 weeks in origin HBeAg positive patients and 82.4% in the first 12 weeks in origin HBeAg negative patients. Age (OR = 1.06, 95% CI = 1.02–1.10; p=0.003), the HBsAg level (OR = 2.21, 95% CI = 1.47–3.32; p<0.001), and positive origin HBeAg status (OR = 0.32, 95% CI = 0.14–0.74; p=0.008) were predictive factors to virologic relapse. HBV DNA level (OR = 1.34, 95% CI = 1.13–1.58; p<0.001) was predictive factor to retreatment. Conclusions. NA cessation is safe under supervision. Age, HBsAg level, and origin HBeAg status can be predictive factors for virologic relapse. The study was submitted to ClinicalTrials.gov Protocol Registration and Results System with the assigned NCT ID NCT02883647.